Peace and Prosperity: An Empirical Analysis Using GPI and GDP per Capita - Yacoubian, Leandro Jorge; Garcia, Daniel Santo Padilla; Silva, Bruno Nogueira; Carvalho, George Harrison Ferreira de; Ketenchian, Grigor Sahak (Revista JRG de Estudos Acadêmicos, 2025)
This paper investigates the empirical relationship between national peacefulness and economic wealth using recent cross-sectional data. By combining Global Peace Index (GPI) scores for 2023 with GDP per capita figures from the World Bank for the same year, the study analyzes a stratified sample of thirty countries divided into three groups: the ten most peaceful, ten mid-ranked, and the ten least peaceful countries. Descriptive statistics, summary measures, and a scatter plot reveal a clear pattern indicating that higher levels of peacefulness are generally associated with higher national income. The Pearson correlation coefficient for the full sample is –0.7544, confirming a strong negative linear relationship between GPI scores and GDP per capita. Although outliers such as Portugal, Slovenia, the United Arab Emirates, and the United States illustrate that peace and prosperity do not always align perfectly, the overall trend remains robust. These findings reinforce the theoretical claim that peaceful environments promote economic development by reducing the costs associated with conflict and insecurity, enhancing governance, and attracting investment. The paper also highlights that peace alone is not sufficient: factors such as governance quality, resource endowments, and technological capacity shape how peace translates into wealth. The results offer valuable insights for policymakers, suggesting that promoting peacefulness should be integral to development strategies aimed at sustainable growth. Future research could build on this evidence by employing panel data to track peace–prosperity dynamics over time and by incorporating broader development metrics beyond GDP per capita.